Prospective Evaluation of Postoperative Penile Rehabilitation: Penile Length/Girth Maintenance 1 Year Following Coloplast Titan Inflatable Penile Prosthesis. (14th April 2015) - Henry, Gerard D.; Carrion, Rafael; Jennermann, Caroline; Wang, Run
Abstract Introduction The most prevalent long‐term complaint after successful inflatable penile prosthesis (IPP) surgery is reduction of penile length. The purpose of this study was to evaluate penile measurements in patients whose implantation experience included the aggressive new length measurement technique (NLMT) coupled with postoperative IPP rehabilitation (daily inflation) of the implant for 1 year. Moreover, we aimed to document objective data concerning dimensional changes of the phallus over time. Postoperative IPP rehabilitation has been discussed and presented at meetings, but no multi‐institutional prospective data have been published. Aim Our goal was to assess results using the Coloplast Titan IPP, with NLMT, and postoperative rehabilitation. Methods After IRB approval, we conducted a prospective, three‐center study of 40 patients who underwent IPP placement, with NLMT for end organ failure erectile dysfunction with the Coloplast Titan IPP. The patient was instructed to inflate daily for 6 months and then inflate maximally for 1–2 hours daily for 6–12 months. Fifteen penile measurements were taken before and immediately after surgery and at follow‐up visits. Main Outcome Measure Penile length measurements after implantation compared with 12 months postimplantation. Results Penile measurement changes were statistically significantly improved at 12 months as compared with immediately postoperative and at 6 months. A total of 64.5% of subjects were satisfied with their length at 1 year, and 74.2% had perceived penile length that was longer (29%) or the same (45.2%) as prior to the surgery; 61.3% and 16.1% of subjects had increased and unchanged satisfaction, respectively, with penile length as compared with prior to IPP surgery. All but two subjects (93.4%) were satisfied with the overall function and dimensions of their IPP. Conclusion This study suggests using the Coloplast Titan IPP with aggressive cylinder sizing, and a postoperative penile rehabilitation inflation protocol may help optimize patient satisfaction and erectile penile measurements. Henry GD, Carrion R, Jennermann C, and Wang R. Prospective evaluation of postoperative penile rehabilitation: Penile length/girth maintenance 1 year following coloplast titan inflatable penile prosthesis. J Sex Med 2015;12:1298–1304.